(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
The Present Study Aims At Uncovering The Relationship Between The Level Of Ambition And Self-Learning And The Extent Of The Contribution Of The Specialization Factor In Creating Differences In This Relationship. We Relied On A Sample Of 300 Students And Two Measurement Tools, Guglimeno). , And The Descriptive Descriptive Approach Was Adopted, And Statistical Processing Was Done Using The Statistical Program (Spss). The Results Were As Follows: 1-There Is A Statistically Significant Relation Between The Level Of Ambition And Its Relation To Self-Learning Among Secondary School Students 2-There Are Statistically Significant Differences In The Level Of Ambition Level Among Secondary School Students Due To The Specialization Variable. 3-There Are Statistically Significant Differences In Level And Self - Learning Among Secondary School Students Due To Specialization Variable Keywords - Level Of Ambition, Self-Learning, Third Secondary Students.